How has the University Community Been Coping During the COVID-19 Pandemic? An Iranian Survey - Ahmadi, Fereshteh; Cetrez, Önver A.; Akhavan, Sharareh; Khodayarifard, Mohammad; Zandi, Saeid (Frontiers in Sociology, 2022)
Objectives: The present study, one of the first to look at COVID-19 and coping in Iran, aimed at mapping, describing and understanding the coping methods academics employ as protective resources to deal with the psychological challenges and social isolation during the COVID-19 pandemic. We specifically aimed at identifying the meaning-making coping methods used and understanding the influence of culture. The guiding research question has been: Are there differences in meaning-making coping methods by gender, age group, work/student status, and place of residence? Design: The study, which used convenience sampling, was a quantitative inquiry. It employed a modified version of the RCOPE scale among faculty/staff members and students in Iran (n = 196, 75% women). Results: The most frequently used coping method among all subgroups of the study sample was thinking that life is part of a greater whole, followed by praying to Allah/God. The least used coping methods were the negative religious ones. Gender differences were found for being alone and contemplating, stronger for men. Thinking that life is part of a greater whole was found mainly among on-campus students. Praying to Allah/God was most common among the youngest staff and students, as well as among women. Two segments of respondents were discovered—the Theists and Non-theists—where the former used more religious coping methods, were more likely to be women, older staff and students, on-campus students, married, have children, and lived in capital. Conclusions: Our conclusion is that the RCOPE methods, which include religious and spiritual meaning-making methods, are of great importance to the studied Iranian informants. However, they use some secular existential meaning-making coping strategies too. This is explained by the role of religion in the larger orientation system and frame of reference in parallel with a secular worldview. Further, a sharp distinction between religious and secular worldviews was not found, which is explained by the fact that secular norms are hardly internalized in ways of thinking in Iran.